2014 IEEE 7th International Workshop on Requirements Engineering and Law (RELAW) 2014
DOI: 10.1109/relaw.2014.6893479
|View full text |Cite
|
Sign up to set email alerts
|

On lawful disclosure of personal user data: What should app developers do?

Abstract: The proliferation of mobile devices and apps together with the increasing public interest in privacy and data protection matters necessitate a more careful precaution for legal compliance. As apps are becoming more popular, app developers can expect an increased scrutiny of privacy practices in the future. In this paper, we focus on the problem of the disclosure of personal data to third parties and the role of app developers to enhance user privacy and data protection in the app ecosystem. We discuss the EU d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…While there is research on making PPs understandable for end users [34,58,72], there is minimal research on helping developers craft PPs. The lack of support can be seen in the wild, where there are still numerous apps without PPs [77] as well PPs that contain misleading and contradictory statements [7].…”
Section: Supporting Privacy Policy Creation Tasksmentioning
confidence: 99%
“…While there is research on making PPs understandable for end users [34,58,72], there is minimal research on helping developers craft PPs. The lack of support can be seen in the wild, where there are still numerous apps without PPs [77] as well PPs that contain misleading and contradictory statements [7].…”
Section: Supporting Privacy Policy Creation Tasksmentioning
confidence: 99%
“…As Roeser [3] notes: “Engineers can influence the possible risks and benefits more directly than anybody else.” However, despite the promise, research has shown that developers of all shades and hues generally lack the competence to deal effectively with privacy management [4,5,6,7] and that the difficulties of complying with regulation are likely to grow considerably [8]. Traditionally, developers are faced with a couple of options.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these tools cannot be integrated within the engineering lifecycle. In consequence, research has shown [16]- [19] that developers and engineers (who usually are not privacy-savvy at all), find privacy and data protection alien to their work and, most importantly, seldom use privacy management tools, as they find these are more oriented to the legal arena rather than to the engineering activities. Same research has encountered that they will be more akin to take decisions that protect privacy and data protection when the process is embedded within their usual development workflow and tools.…”
Section: Automating Privacy Managementmentioning
confidence: 99%